Radioactivity: Sustainable Materials and Innovative Techniques - Saleh, Hosam M.; Dawoud, Mohammad Mahmoud (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on radioactivity and applied research on the gamma irradiation of marjoram and the transfer of natural radionuclides to date palm plants. Sustainable techniques such as phytoremediation and bio-sorption were used in the treatment of radioactive waste, and sustainable materials were used in the immobilization of radioactive waste and radiation shielding. Natural radioactivity was investigated in common construction materials.